Pengaruh Pendampingan Mp-Asi Berdasarkan Aspek Pengetahuan Ibu Dan Praktik Pemberian Mp-Asi Balita Gizi Kurang Usia 6-24 Bulan Di Wilayah Kerja Puskesmas Ngawen Kabupaten Blora - Intan Mulyani Suparjo; Susi Tursilowati; Arintina Rahayuni (JURNAL RISET GIZI, 2016)
Background: Under Weight is a health problem that occurs in developing countries like Indonesia. The prevalence of malnutrition nationally as much as 19.6%. The prevalence of under weight in Central Java 18% and in CHC Ngawen 14.8%.Objective: To describe the effect of nutritional assistance based on affect of mothers knowledge and feeding practices for children under weight 6-24 months age in CHC of Ngawen Blora.Methods: There was a quasi-experimental design pre and post test control group gesign with 38 samples. The intervention group received nutrition assistance for 1 month with 3 sessions (intensive, reinforcement, self). Data analysis used Annova Repeated Measure.Results: The average knowledge of the mother before and after assistance, was 78.0 and 89.26. The average of feeding practice before and after assistance was 70.62 and 85.6.Conclusion: There were differences in the knowledge scores of mothers and provision of complementary feeding practices between the control and intervention groups after being given assistance (p=0.094 and p = 0.073). Research for the effect of nutrition assistance program should be implemented to the nutritional status of children 6-24 months ages malnutrition